OPTIMASI PEMANFAATAN ASET GEDUNG BALAI PELATIHAN KESEHATAN DINAS KESEHATAN PROVINSI JAWA BARAT MELALUI STRATEGI PEMASARAN - Nurlaila Fadjarwati; Nandi Koswara (Politeknik Negeri Sriwijaya, 2014)
This research on asset optimization through marketing strategies in Balai Pelatihan Kesehatan (BAPELKES) Health Departement of West Java Province. This purpose of this study is to examine depth optimizing assets Bapelkes Bandung building using 7P marketing mix analysis. The method used in this research is descriptive method. Where as techniques of data collection in this research is primary data and secondary data collection. Techniques of primary data collection was done with observation at the assets, interview to administrator and users. Techniques of secondary data collection was done with literature study and documentation study. Based on the result of research on the marketing mix in optimizing utilization the assets Bapelkes Bandung building use 7P marketing mix of product, price, place, promotion, people, process and physical evidence. The author has got the conclusion of the tools used for promotion in accordance with Bapelkes Bandung.